Analysis of Translation Techniques of Grand Sheikh Al-Azhar's Speeches on Sanad Media's YouTube Channel - Sandriwan, Andri; Syihabuddin, Syihabuddin; Supriadi, Rinaldi (Al-Manar, 2024)
AbstractIn the digital age, YouTube serves as a major resource for learning Arabic. Language and cultural variances necessitate the need for translation to comprehend the messages conveyed in the videos. The purpose of this study is to analyze translation techniques in the speech of the Grand Sheikh of Al-Azhar on the YouTube channel of Sanad Media Account, specifically focusing on the translated text entitled "The Urgency of Values in the Brotherhood Charter in Achieving World Peace". The research method uses a qualitative approach with content analysis, taking data from YouTube videos and analyzing translation techniques from Arabic to Indonesian by referring to Molina and Albir's theory. The results of the analysis show that 14 out of 19 translation techniques suggested by Al Farisi based on Molina & Albir's theory are used in translating Arabic texts from the subtitles of Sanad Media Account's YouTube videos. The most frequently used translation technique is transposition, with a frequency of 77 (19.74%). It is followed by the calce technique with a frequency of 60 (15.38%) and reduction with a frequency of 56 (14.36%). The amplification and linguistic amplification techniques have almost the same frequency, namely 37 (9.49%) and 34 (8.72%). The mutation technique has a frequency of 31 (7.95%), while modulation has a frequency of 26 (6.67%). Borrowing and matching techniques have lower frequencies, namely 18 (4.62%) and 13 (3.33%). The substitution technique has a frequency of 10 (2.56%). Then, literal, adaptation, and generalization techniques have the same frequency, namely 9 (2.31%) and linguistic compression techniques have the lowest frequency, 1 (0.26%). On the other hand, particularization, description, compensation, variation, and discursive techniques have no frequency because they are not used in the translation. Keywords: Arabic Speech; Translation Analysis; Transposition; YouTube